Helminthes of Goby Fish of the Hryhoryivsky Estuary (Black Sea, Ukraine) - Kvach, Yu. (Вестник зоологии, 2002)
In the paper the data about the helminthofauna of Neogobius melanostomus, N. ratan, N. fluviatilis, Mesogobius batrachocephalus, Zosterisessor ophiocephalus, and Proterorhynus marmoratus in the Hryhoryivsky Estuary are presented. The fauna of gobies’ helmint hes consist of 10 species: 5 trematods (Cryptocotyle concavum met., C. lingua met., Pygidiopsis genata met., Acanthostomum imbutiforme met.), Asymphylodora pontica, one cestoda (Proteocephalus gobiorum), 2 nematods (Streptocara crassicauda l., Dichelyne minutus), and 2 acanthocephalans (Acanthocephaloides propinquus, Telosentis exiguus). Only one of trematods species was presented by adult stage. The modern fauna of helminthes and published data are compared. The relative stability of the goby fish helminthofauna of the Estuary is mentioned.